2019
DOI: 10.18805/lr-428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diverse cowpea [Vigna unguiculata (L.) Walp.] germplasm accessions for drought tolerance

Abstract: The genetic potential for drought tolerance in cowpea within the small holder sector has not been fully exploited in South Africa. Thus, a drought evaluation experiment was conducted at the ARC-VOP to evaluate 28 cowpea germplasm accessions including two controls viz. IT96D-602 (drought tolerant) and TVU7778 (susceptible to drought) in the drought screening house using plastic box evaluation method in January, 2017. Genotypes raised for three weeks were subjected to 5 weeks of water stress treatment to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…High anthocyanin in selenite primed Nerica U7 could be responsible for high chlorophyll contents during water stress which might be as a result of the tolerant ability of the cultivar. Genetic variability and differential respond observed in plants could be due to their genotypes (Nkoana et al, 2019). Means along the row with the same alphabet are not significantly different.…”
Section: Investigating the Effectiveness Of Selenite On Drought Stresmentioning
confidence: 89%
“…High anthocyanin in selenite primed Nerica U7 could be responsible for high chlorophyll contents during water stress which might be as a result of the tolerant ability of the cultivar. Genetic variability and differential respond observed in plants could be due to their genotypes (Nkoana et al, 2019). Means along the row with the same alphabet are not significantly different.…”
Section: Investigating the Effectiveness Of Selenite On Drought Stresmentioning
confidence: 89%
“…Drought is defined as a sustained period without significant rainfall, or when the crops do not receive enough moisture for growth and development (Bodner et al 2015). Water stress during early plant establishment, flowering and pod filling stages severely affects productivity (Nkoana et al 2019). Although cowpea is drought tolerant when compared to other crops, severe drought, especially during pod setting and grain filling stages, can hamper the production of the crop (Singh and Raja Reddy 2011).…”
Section: Abiotic Constraints In Cowpea Productionmentioning
confidence: 99%
“…Drought is a complex quantitative trait, and breeding for drought tolerance combines selection for yield with expression of physiological traits correlated with drought tolerance to repeatable controlled stress environments. Several studies (Barrera-Figueroa et al 2011;Farooq et al 2012;Nkoana et al 2019) have indicated the presence of genetic variability for drought tolerance in cowpea, at different growth stages (reproductive, seedling and vegetative stages) using physiological and morphological traits. Progress towards cultivar development for drought tolerance is scarce, due to the complexity of this trait.…”
Section: Genetic Diversity For Drought Tolerance Breedingmentioning
confidence: 99%
“…Crop productivity can be increased by the application of suitable amount of water wither saline or not under specific condition (Ebtisam et al, 2015). Water is considered as one of the most important environmental factors that reduces crop productivity more than any other factor (Saxena et al, 2017;Nkoana et al, 2019;Kiymaz et al, 2019;Jahantigh et al, 2019 andMiladinov et al, 2020). Belachew et al (2019) recorded significant effect of water deficit on the yield components in faba bean.…”
Section: Introductionmentioning
confidence: 99%